Marginal Revolution: The Impact of Transnational Education on Higher Education in China - Ding, Xiaojiong (International Higher Education, 2020)
Transnational education (TNE) in China has been closely related to the concept of capacity building. However, its relative academic weakness and the way it operates impede knowledge transfer and organizational learning. After 30 years of development, TNE is still at the periphery of the Chinese higher education system, with only a marginal impact on capacity building.